The Coserian theory of metaphor and Conceptual Metaphor Theory: affinities and divergences - Rodríguez, Fernando G. (Energeia : Online-Zeitschrift für Sprachwissenschaft, Sprachphilosophie und Sprachwissenschaftgeschichte, 2025)
The Coserian conception of metaphor and that of cognitive linguistics have been the subject of attempts at rapprochement, founded on points of convergence that, when considered from their theoretical frameworks, begin to appear less akin. This study aims to re-examine the topics of this comparison and take the analysis a step further, considering the items of concept, integral linguistics, semantics, corporality, and mental images, all of which can be identified, in one way or another, in the two perspectives addressed here. The paper presents, first, a succinct overview of the principal ideas of Coseriu’s linguistic theory regarding his conception of metaphor. Second, it provides a panoramic account of cognitive linguistics, emphasising those aspects most directly related to creativity and metaphor (particularly the Conceptual Metaphor Theory). Third, within the general framework of Coserian philosophy of language and the psycho-gnoseological commitments of cognitive linguistics, it contrasts the notion of image schema, the cognitive basis of the conceptual metaphor proposal, and Coseriu’s notion of metaphoric creation, in order to demonstrate that all the apparent points of convergence between these two theoretical approaches, apart from certain focal similarities, cease to coincide once their respective theoretical frameworks and objectives are fully taken into account. The Coserian conception of metaphor and that of cognitive linguistics have been the subject of attempts at rapprochement, founded on points of convergence that, when considered from their theoretical frameworks, begin to appear less akin. This study aims to re-examine the topics of this comparison and take the analysis a step further, considering the items of concept, integral linguistics, semantics, corporality, and mental images, all of which can be identified, in one way or another, in the two perspectives addressed here. The paper presents, first, a succinct overview of the principal ideas of Coseriu’s linguistic theory regarding his conception of metaphor. Second, it provides a panoramic account of cognitive linguistics, emphasising those aspects most directly related to creativity and metaphor (particularly the Conceptual Metaphor Theory). Third, within the general framework of Coserian philosophy of language and the psycho-gnoseological commitments of cognitive linguistics, it contrasts the notion of image schema, the cognitive basis of the conceptual metaphor proposal, and Coseriu’s notion of metaphoric creation, in order to demonstrate that all the apparent points of convergence between these two theoretical approaches, apart from certain focal similarities, cease to coincide once their respective theoretical frameworks and objectives are fully taken into account. The Coserian conception of metaphor and that of cognitive linguistics have been the subject of attempts at rapprochement, founded on points of convergence that, when considered from their theoretical frameworks, begin to appear less akin. This study aims to re-examine the topics of this comparison and take the analysis a step further, considering the items of concept, integral linguistics, semantics, corporality, and mental images, all of which can be identified, in one way or another, in the two perspectives addressed here. The paper presents, first, a succinct overview of the principal ideas of Coseriu’s linguistic theory regarding his conception of metaphor. Second, it provides a panoramic account of cognitive linguistics, emphasising those aspects most directly related to creativity and metaphor (particularly the Conceptual Metaphor Theory). Third, within the general framework of Coserian philosophy of language and the psycho-gnoseological commitments of cognitive linguistics, it contrasts the notion of image schema, the cognitive basis of the conceptual metaphor proposal, and Coseriu’s notion of metaphoric creation, in order to demonstrate that all the apparent points of convergence between these two theoretical approaches, apart from certain focal similarities, cease to coincide once their respective theoretical frameworks and objectives are fully taken into account. The Coserian conception of metaphor and that of cognitive linguistics have been the subject of attempts at rapprochement, founded on points of convergence that, when considered from their theoretical frameworks, begin to appear less akin. This study aims to re-examine the topics of this comparison and take the analysis a step further, considering the items of concept, integral linguistics, semantics, corporality, and mental images, all of which can be identified, in one way or another, in the two perspectives addressed here. The paper presents, first, a succinct overview of the principal ideas of Coseriu’s linguistic theory regarding his conception of metaphor. Second, it provides a panoramic account of cognitive linguistics, emphasising those aspects most directly related to creativity and metaphor (particularly the Conceptual Metaphor Theory). Third, within the general framework of Coserian philosophy of language and the psycho-gnoseological commitments of cognitive linguistics, it contrasts the notion of image schema, the cognitive basis of the conceptual metaphor proposal, and Coseriu’s notion of metaphoric creation, in order to demonstrate that all the apparent points of convergence between these two theoretical approaches, apart from certain focal similarities, cease to coincide once their respective theoretical frameworks and objectives are fully taken into account. La concepción coseriana de la metáfora y la de la lingüística cognitiva han sido objeto de intentos de acercamiento, basados en puntos de convergencia que, al ser considerados desde sus respectivos marcos teóricos, comienzan a mostrarse menos afines. Este estudio tiene como objetivo reexaminar los tópicos de dicha comparación y llevar el análisis un paso más allá, considerando los elementos de concepto, lingüística integral, semántica, corporeidad e imágenes mentales, todos los cuales pueden identificarse, de una u otra manera, en las dos perspectivas abordadas aquí. El artículo presenta, en primer lugar, una visión sucinta de las ideas principales de la teoría lingüística de Coseriu en relación con su concepción de la metáfora. En segundo lugar, ofrece un panorama de la lingüística cognitiva, enfatizando aquellos aspectos más directamente relacionados con la creatividad y la metáfora (particularmente, la Teoría de la Metáfora Conceptual). En tercer lugar, dentro del marco general de la filosofía del lenguaje coseriana y de los compromisos psico-gnoseológicos de la lingüística cognitiva, contrasta la noción de image schema, base cognitiva de la propuesta de metáfora conceptual, y la noción de creación metafórica de Coseriu, con el fin de demostrar que todos los aparentes puntos de convergencia entre estos dos enfoques teóricos, más allá de ciertas similitudes focales, dejan de coincidir una vez que se consideran plenamente sus respectivos marcos teóricos y objetivos. The Coserian conception of metaphor and that of cognitive linguistics have been the subject of attempts at rapprochement, founded on points of convergence that, when considered from their theoretical frameworks, begin to appear less akin. This study aims to re-examine the topics of this comparison and take the analysis a step further, considering the items of concept, integral linguistics, semantics, corporality, and mental images, all of which can be identified, in one way or another, in the two perspectives addressed here. The paper presents, first, a succinct overview of the principal ideas of Coseriu’s linguistic theory regarding his conception of metaphor. Second, it provides a panoramic account of cognitive linguistics, emphasising those aspects most directly related to creativity and metaphor (particularly the Conceptual Metaphor Theory). Third, within the general framework of Coserian philosophy of language and the psycho-gnoseological commitments of cognitive linguistics, it contrasts the notion of image schema, the cognitive basis of the conceptual metaphor proposal, and Coseriu’s notion of metaphoric creation, in order to demonstrate that all the apparent points of convergence between these two theoretical approaches, apart from certain focal similarities, cease to coincide once their respective theoretical frameworks and objectives are fully taken into account. The Coserian conception of metaphor and that of cognitive linguistics have been the subject of attempts at rapprochement, founded on points of convergence that, when considered from their theoretical frameworks, begin to appear less akin. This study aims to re-examine the topics of this comparison and take the analysis a step further, considering the items of concept, integral linguistics, semantics, corporality, and mental images, all of which can be identified, in one way or another, in the two perspectives addressed here. The paper presents, first, a succinct overview of the principal ideas of Coseriu’s linguistic theory regarding his conception of metaphor. Second, it provides a panoramic account of cognitive linguistics, emphasising those aspects most directly related to creativity and metaphor (particularly the Conceptual Metaphor Theory). Third, within the general framework of Coserian philosophy of language and the psycho-gnoseological commitments of cognitive linguistics, it contrasts the notion of image schema, the cognitive basis of the conceptual metaphor proposal, and Coseriu’s notion of metaphoric creation, in order to demonstrate that all the apparent points of convergence between these two theoretical approaches, apart from certain focal similarities, cease to coincide once their respective theoretical frameworks and objectives are fully taken into account.